Entrepreneurship Development in the Era of Disruptive Technology: (Case Study in Denpasar City and Bandung City) - Mangeswuri, Dewi Restu (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Indonesia has recently seen a disruptive technological period, one in which technology causes numerous changes in daily life. The existence of entrepreneurship in the regions is one of the many social effects of disruptive technologies. This essay explores how technology has helped businesses flourish, particularly in Denpasar and Bandung. Due to their potential to foster entrepreneurship by employing current technologies, both cities were selected. This study will describe the entrepreneurship development in the era of disruptive technology in the both cities. The findings of this study demonstrate that technology has a significant impact on the growth of new enterprises or new entrepreneurs in the regions. Through the application of technology, entrepreneurship has enormous potential for growing market share. The majority of them, however, still have extremely limited digital capabilities, making it impossible for them to fully exploit the trend of economic digitization. The government, both central and regional, needs to take action to deal with disruptive technological advancements in order to foster the growth of entrepreneurship by using technology.